Madecassoside Protects Against LPS-Induced Acute Lung Injury via Inhibiting TLR4/NF-κB Activation and Blood-Air Barrier Permeability - Peng, Lu-Yuan; Shi, Hai-Tao; Yuan, Meng; Li, Jing-He; Song, Ke; Huang, Jiang-Ni; Yi, Peng-Fei; Shen, Hai-Qing; Fu, Ben-Dong (Frontiers in Pharmacology, 2020)
Madecassoside (MA), a crucial ingredient of Centella asiatica, has been reported to exhibit a variety of bioactivities, including antipulmonary fibrosis, and antiinflammatory effects. Here we aimed to elucidate the protective effects and underlying mechanisms of MA on LPS-induced acute lung injury (ALI). The mice were treated with MA for one week and then received intratracheal of LPS to establish the ALI model. Then we evaluated the pathological changes by haematoxylin and eosin staining and measured the levels of proinflammatory cytokines and myeloperoxidase (MPO) by ELISA, the transcriptional level of tight junction proteins by qRT-PCR, as well as the expression of Toll-like receptor4/Nuclear factor kappa-B (TLR4/NF-κB) pathway by Western blot. The results showed that MA significantly inhibited LPS-induced pathological damages, lung edema, MPO, and proinflammatory cytokines production. Furthermore, MA obviously repaired alveolar epithelium integrity showing by reduced secretion of total proteins in the BALF and enhanced mRNA expression of tight junction as Occludin and zonula occludens-1 (ZO-1) comparing to LPS. Further research showed that LPS stimulation activated the TLR4/NF-κB signaling pathway and the activation was inhibited by MA. In conclusion, these data indicated that MA had protective effects against LPS-induced ALI. The therapeutic mechanisms may be associated with reducing the alveolar epithelium permeability and inflammatory response via repressing the activation of TLR4/NF-κB pathway.